STUDI PERBANDINGAN BIOSURFAKTAN Pseudomonas aeruginosa IA7d DAN SURFAKTAN SINTETIK Tween-80 DALAM BIODEGRADASI SOLAR OLEH MIKROBA PERAIRAN PELABUHAN TANJUNG PERAK SURABAYA - Ni’matuzahroh Ni’matuzahroh; Arif Yachya; Mulyadi Tanjung (The East Java Biological Society, 2006)
This research aimed to know the influence of addition crude product Pseudomonas aeruginosa IA7d biosurfactant from substrate hexadecane and diesel fuel in supporting activity of diesel fuel biodegradation and both potention to replace synthetic surfactant for hydrocarbon remediation. Biodegradation test was done by experimental in laboratory scale by Tween-80 as synthetic surfactant comparator. Growth culture was from seawater of Tanjung Perak Harbor Surabaya include various microbe types in its. 2% ( w/v) of diesel fuel and three surfactants test (0.70% w/v crude product P. aeruginosa IA7d biosurfactant from hexadecane substrate; 60,69% w/v crude product P. aeruginosa IA7d biosurfactant from diesel fuel substrate; and 0.10% w/v synthetic surfactant Tween 80) at uniform surface tension of surfactant solution (54.03 mN/m) were added into 30 ml seawater sample. Cultures were incubated at room temperature (30 °C) during 14 days with shaking (90 rpm). Result of biodegradation test showed the third addition of surfactants test had an effect on acceleration of diesel fuel biodegradation activity that proved at the increased of microbial count (bacterium, yeast, and mould) and decreased of diesel fuel concentration was shown by chromatograms area of diesel fuel. Highest degradation was successively reached by culture got crude product P. aeruginosa IA7d biosurfactant from diesel fuel substrate (88.034%), crude product P. aeruginosa IA7d biosurfactant from hexadecane substrate (80.908%), synthetic surfactant Tween-80 (54.732%), and control that was without addition surfactant test (0.132%). Base on number of microbial count, percentage of decreasing chromatogram peaks of diesel fuel from each surfactant test, and price substrate produce (diesel fuel and hexadecane) among both crude product P. aeruginosa IA7d biosurfactant, known that the crude product P. aeruginosa IA7d biosurfactant from diesel fuel substrate had highest ability acceleration to biodegradation activity on diesel fuel and had a potency to replace synthetic surfactant for remediation hydrocarbon application in environment.